Comparison of Efficacy and Efficiency of Trans-Nasal Spheno-Palatine Ganglion Block for the Management of Post-Dural Puncture Headache - Singh, Sanjeev; Mishra, Rachna; Deigheidy, Ehab Mahrous (Journal of the Portuguese Society of Anesthesiology, 2025)
Introduction: Epidural blood patch (EBP) is the standard treatment for refractory post-dural puncture headache (PDPH) following caesarean section (C/s), but is invasive and associated with rare yet serious complications. A minimally invasive alternative is the trans-nasal sphenopalatine ganglion block (TNSPGB). This study compared the efficacy and efficiency of TNSPGB in achieving pain reduction, defined as a decrease of ≥2 points on the Numeric Rating Scale (NRS). Methods: This single-centre, prospective interventional study was conducted after ethical approval. Forty-four patients with PDPH were allocated equally into two groups. Group I received EBP, and Group II received TNSPGB with 1.4 mL local anaesthetic (0.7 mL lidocaine 4% plus 0.7 mL ropivacaine 0.5%). Hemodynamic variables, pain scores, onset and duration of analgesia, adverse effects, total paracetamol dose, patient satisfaction, and hospital stay within 24 h were recorded. Results: Baseline pain scores were comparable between groups (p=0.457). The onset of analgesia was significantly faster in Group II than Group I (18.2±4.4 vs 62.3±11.8 min, p<0.001) and they reported lower NRS during 1 hour. After that, Group I reported significantly lower NRS at 2 and 4 hours (p< 0.001). At 8, 12 and 24 hours, pain scores were similarly low (NRS-1 to 3) in both groups (all p>0.05). There were no significant differences between the groups regarding hemodynamic, pain scores, duration of analgesia, adverse effects, rescue analgesia, and patient satisfaction within 24 hours after the intervention. Conclusion: TNSPGB with local anaesthetics provides effective, rapid, safe, and minimally invasive pain relief for PDPH following C/s and is comparable to EBP.